Structural and electrical characterization of AuPtAlTi ohmic contacts to AlGaN/GaN with varying annealing temperature and Al content - Fay, Mike W.; Han, Y.; Brown, Paul D.; Harrison, Ian; Hilton, K.P.; Munday, A.; Wallis, D.; Balmer, R.S.; Uren, M.J.; Martin, T. (American Institute of Physics, 2008)
The effect of varying annealing temperature and Al layer thickness on the structural and electrical characteristics of AuPtAlTi/AlGaN/GaN ohmic contact structures has been systematically investigated. The relationship between annealing temperature, Al content, interfacial microstructure, surface planarity and contact resistance is examined. In particular, the presence of a detrimental low temperature Pt-Al reaction is identified. This is implicated in both the requirement for a higher Al:Ti ratio than is required for related AuPdAlTi contact schemes and through the degraded temperature dependent resistance behaviour of the annealed AuPtAlTi contacts.